Connective Tissue Growth Factor Promotes Pulmonary Epithelial Cell Senescence and Is Associated with COPD Severity. (30th March 2017) - Jang, Jun-Ho; Chand, Hitendra S.; Bruse, Shannon; Doyle-Eisele, Melanie; Royer, Christopher; McDonald, Jacob; Qualls, Clifford; Klingelhutz, Aloysius J.; Lin, Yong; Mallampalli, Rama; Tesfaigzi, Yohannes; Nyunoya, Toru
ABSTRACT: The purpose of this study was to determine whether expression of connective tissue growth factor (CTGF) protein in chronic obstructive pulmonary disease (COPD) is consistent in humans and animal models of COPD and to investigate the role of this protein in lung epithelial cells. CTGF in lung epithelial cells of ex-smokers with COPD was compared with ex-smokers without COPD by immunofluorescence. A total of twenty C57Bl/6 mice and sixteen non-human primates (NHPs) were exposed to cigarette smoke (CS) for 4 weeks. Ten mice of these CS-exposed mice and eight of the CS-exposed NHPs were infected with H3N2 influenza A virus (IAV), while the remaining ten mice and eight NHPs were mock-infected with vehicle as control. Both mRNA and protein expression of CTGF in lung epithelial cells of mice and NHPs were determined. The effects of CTGF overexpression on cell proliferation, p16 protein, and senescence-associated β-galactosidase (SA-β-gal) activity were examined in cultured human bronchial epithelial cells (HBECs). In humans, CTGF expression increased with increasing COPD severity. We found that protein expression of CTGF was upregulated in lung epithelial cells in both mice and NHPs exposed to CS and infected with IAV compared to those exposed to CS only. When overexpressed in HBECs, CTGF accelerated cellular senescence accompanied by p16 accumulation. Both CTGF and p16 protein expression in lung epithelia are positively associated with the severity of COPD in ex-smokers. These findings show that CTGF is consistently expressed in epithelial cells of COPD lungs. By accelerating lung epithelial senescence, CTGF may block regeneration relative to epithelial cell loss and lead to emphysema.